Best Practices in Family Life Education Program Evaluation. Issue 3 (29th December 2019) - Hawkins, Alan J.; Clyde, Tiffany L.; Doty, Jennifer L.; Avellar, Sarah
Abstract : Program evaluation should be integral to family life education (FLE), but program administrators face common barriers, including expense, lack of evaluation expertise, and fear of no‐effects findings. Thus, the purpose of this article is to provide a primer on feasible best‐practice guidelines for the evaluation of FLE programs. Specifically, we explore four best practices in FLE program evaluation research in real‐world field conditions: (a) clarify upfront the underlying program theory of change or logic model and make research decisions based on this model; (b) adopt a developmental perspective on program evaluation and a mentality of continuous quality improvement; (c) when ready, invest in rigorous impact evaluations with random assignment; and (d) share and synthesize evaluation work to strengthen the field. A theme woven throughout these best practices is for program administrators to collaborate with experienced evaluation researchers to deal with challenging issues. Following these best‐practice guidelines will help program administrators overcome common barriers and conduct evaluation work that strengthens their programs over time and enriches the lives of families.